2020
DOI: 10.1101/2020.06.30.20142877
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying the impact of US state non-pharmaceutical interventions on COVID-19 transmission

Abstract: COVID-19 is an ongoing public health emergency. Without a vaccine or effective antivirals, non-pharmaceutical interventions form the foundation of current response efforts. Quantifying the efficacy of these interventions is crucial. Using mortality data and a classification guide of state level responses, we relate the intensity of interventions to statistical estimates of transmission, finding that more stringent control measures are associated with larger reductions in disease proliferation. Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 21 publications
4
26
0
Order By: Relevance
“…While there is uncertainty in our epidemic projections, our results are consistent with previously published studies [18,[26][27][28] and are intended to serve as guideposts for deliberations regarding the potential relative impact of different school reopening scenarios in the U.S.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…While there is uncertainty in our epidemic projections, our results are consistent with previously published studies [18,[26][27][28] and are intended to serve as guideposts for deliberations regarding the potential relative impact of different school reopening scenarios in the U.S.…”
Section: Discussionsupporting
confidence: 86%
“…The results show that alternating school cohort scenarios can significantly avert the total number of cases by approximately 60M and 28M for the Fewer Open Workplaces and More Open Workplaces, respectively. The results are consistent with previous studies [18,[26][27][28] that have shown that non-pharmaceutical interventions can delay the peak of an outbreak (i.e., flatten the curve) and reduce the total number of cases over the same time frame. Furthermore, the offsite scenario provides the largest benefit by averting the greatest number of cases followed by the 40% scenarios.…”
Section: Cases Deaths and Hospitalizations Avertedsupporting
confidence: 92%
“…Two factors that may be of importance for the effect is population density and how widely spread the virus was prior to schools closing. A study of US districts show that transmission of SARS-CoV-2 increases with population density (Korevaar et al, 2020). This suggests that when people live close, each person interact with more people and hence are more likely to transmit the virus.…”
Section: S4 Heterogeneity Analysismentioning
confidence: 99%
“…To first evaluate variation in the burden emerging from the severity of infection outcome, we consider how demography, comorbidity, and access to care might modulate the age profile of SARS-CoV-2 morbidity and mortality 2 - 4 . Subnational variation in the distribution of high risk age groups indicates considerable variability, with higher burden expected in urban settings in SSA ( Figure 3A ), where density and thus transmission are likely higher 27 .…”
Section: Severity Of Infection Outcomementioning
confidence: 99%